Pendidikan Inklusi Dalam Strategi Fun Learning di Bimba Rainbow Kids Cisauk-Tangerang - Ika Ika; Rasban Yoyon; Abdul Aziz (Institut Nalanda, 2024)
Inclusive education in early childhood begins by accommodating children's needs, identifying children with special needs, as well as mapping the potential developments and obstacles of children today and in the future. This study aims to analyze the extent to which the implementation of inclusive education in early childhood education institutions in one of the early childhood education institutions in the city of Tangerang. First, researchers collect information about the implementation of inclusive education in early childhood education institutions, the obstacles and constraints experienced, program optimization, and follow-up to the problems encountered by BIMBA Rainbow Kids in providing inclusive education. Then, researchers perform data analysis by enriching information, looking for relationships, comparing, finding patterns based on the original data. The results of this study indicate that the learning strategy used in BIMBA Rainbow Kids Cisauk-Tangerang uses several methods, namely: Fun learning, Small step system, individual system, and variation skill. Learning strategies in early childhood are carried out in a fun way, namely playing while learning.